PENGARUH DISKON, ELECTRONIC WORD OF MOUTH, DAN SHOPPING LIFESTYLE TERHADAP PERILAKU IMPULSE BUYING:(Studi Kasus Pada Pengguna Tiktok Di Kota Bogor) - Nada Azizah Aryanti (2022)
The existence of the Covid-19 pandemic has caused a surge in technology users, especially social media, where people play social media to communicate or find out about a product, so social media and e-commerce are needed which can provide discounts, good electronic word of mouth promotions, and are able to adjust the shopping lifestyle of its users. Tiktok is an application that has two functions at the same time as social media and e-commerce. This study aims to determine, prove, and analyze the effect of discounts on impulse buying, electronic word of mouth on impulse buying, and shopping lifestyle on impulse buying. This research is a quantitative research using primary data sources. The object of this research is Tiktok users in Bogor City who have shopped at the Tiktok Shop. This study used a sample of 146 respondents, with a non-probability sampling method, namely purposive sampling. Data is collected online, distributed using a questionnaire via the Google form. Analysis technique using the PLS (Partial Least Square) analysis method through the SmartPls 3.2 application. The results of this study indicate that: (1) Discounts have an effect on impulse buying with a path coefficient of 0.253 (2) Electronic word of mouth has no effect on impulse buying with a path coefficient of -0.117 (3) Shopping lifestyle has an effect on impulse buying with a path coefficient of -0.117 0.725. With the value of the contribution together with the discount variable, electronic word of mouth, and shopping lifestyle using an Adjusted R-Square value of 0.643 or 64.3% affects impulse buying, and the remaining 35.7% is influenced by other variables.